2023
DOI: 10.26434/chemrxiv-2023-dd1hc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Receptor-Ligand Restraint Schemes for Alchemical Absolute Binding Free Energy Calculations

Abstract: Alchemical absolute binding free energy calculations are of increasing interest in drug discovery. These calculations require restraints between the receptor and ligand to restrict their relative positions and, optionally, orientations. Boresch restraints are commonly used, but they must be carefully selected in order to sufficiently restrain the ligand and to avoid inherent instabilities. Applying multiple distance restraints between anchor points in the receptor and ligand provides an alternative framework w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…, 51 respectively, where they observed that in case of solvent exposed binding pockets or side chain changes between the APO and HOLO structures longer alchemical transformations lead to better free energy estimates. In our case, the correct sampling of the slow degrees of freedom linked to the coupling/decoupling is in part assisted by the HREM sampling of the initial bound state, that helps with 'stiff' dihedrals, and in part by the long nonequilibrium alchemical transformations that tame the dissipation connected to the slow entrance of water solvent molecules in the unfettered cavity of the ligand at low coupling.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…, 51 respectively, where they observed that in case of solvent exposed binding pockets or side chain changes between the APO and HOLO structures longer alchemical transformations lead to better free energy estimates. In our case, the correct sampling of the slow degrees of freedom linked to the coupling/decoupling is in part assisted by the HREM sampling of the initial bound state, that helps with 'stiff' dihedrals, and in part by the long nonequilibrium alchemical transformations that tame the dissipation connected to the slow entrance of water solvent molecules in the unfettered cavity of the ligand at low coupling.…”
Section: Resultsmentioning
confidence: 99%
“…To see if restraining more the ligand during the annihilation gathers better results we also performed the calculations with the Loose-Tight restraint with two "frozen" atoms (see SI Figures 4, 5), the results obtained are similar to the one atom case but worse, this is in contradiction with what observed in ref. 12 where restraining the orientational degrees of freedom gathered better results. So we performed bidirectional calculations with one and two "frozen" atoms (see CI Figures 6,7,8,9), in general they gave worse results for twice the computational cost, but in this case the transformations with two "frozen" atoms, and therefore a restrained rotational degree of freedom, performed better than those with one "frozen" atom in agreement with ref.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations